The expression and regulation of ADAMTS-1, -4, -5, -9, and -15, and TIMP-3 by TGFbeta1 in prostate cells: relevance to the accumulation of versican. - Cross, N; Chandrasekharan, S; Jokonya, N; Fowles, A; Hamdy, F; Buttle, D; Eaton, C (2005)
BACKGROUND: Benign prostatic hyperplasia (BPH) is characterized by a proportional increase in the size of the stromal compartment of the gland, involving alterations to extracellular matrix (ECM) components. Some of these changes have been associated with the activity and expression of transforming growth factor beta1 (TGFbeta1). Versican (chondroitin sulphate proteoglycan-2) is overexpressed in BPH and prostate cancer and potentially contributes to disease pathology. A sub-group of the ADAMTS lineage of metalloproteases possess versican-degrading properties and are potential regulators of proteoglycan accumulation associated with BPH. These enzymes have one major inhibitor in the ECM, tissue inhibitor of metalloproteinases (TIMP)-3. METHODS: The effect of TGFbeta on mRNA expression in prostatic stromal cells was determined by real-time qRT-PCR using primers to ADAMTS-1, -4, -5, -9, -15, versican, and TIMP-3. MMP-inhibitory potential (TIMP activity) of conditioned medium was measured using a fluorometric peptide substrate. RESULTS: Prostatic stromal cell cultures consistently expressed ADAMTS-1, -4, -5, -9, -15 and TIMP-3, in contrast to PC3, DU145, and LNCaP cells which failed to express at least two ADAMTS transcripts. In stromal cells, TGFbeta1 decreased ADAMTS-1, -5, -9, and -15 transcripts and increased ADAMTS-4, versican, and TIMP-3. TGFbeta also increased TIMP activity in conditioned medium. CONCLUSIONS: The induction of versican expression by TGFbeta in BPH stromal cells is in agreement with histological studies. The negative effect of TGFbeta1 on ADAMTS-1, -5, -9, and -15 coupled with increases in their inhibitor, TIMP-3 may aid the accumulation of versican in the stromal compartment of the prostate in BPH and prostate cancer.